Fruição entre telas: design audiovisual aplicado ao serviço de streaming Globoplay - Sousa, Amanda Azevedo (2020)
This research aims to identify how the streaming interfaces can provide forms of audiovisual fruition, we use Globoplay as the object of this research, which is a service derived from the main content producer in Brazil, TV Globo. For this, we use Audiovisual Design, which is a conceptual theoretical model developed by the intersection between the theories of Human-Computer Interaction and Media Studies. This model is opportune to carry out analyzes about the consumption of content through the uses of the interfaces, presenting different focuses to plan strategies in audiovisual products and services. The methodology of this work was carried out by qualitative analysis, using as instruments of data collection the survey of the conditions of the interfaces, the evaluations of the consumers, the interaction relations with the contents, the mapping of the information available online about the programming grid and the service catalog. The results showed that the resources offered by Globoplay allow the fruition at basic levels, through comments and shares. However, there are consumer relations between Globoplay and TV Globo, websites of television programs and digital social networks, which expand the interaction to other levels, although these interactions do not always occur in a planned way. We concluded this work by presenting opportunities for the creation of resources on the interfaces, assigning the domains of interaction to the individual, enabling the planning of the contents together with the forms of audiovisual fruition.